2004
DOI: 10.1117/12.552257
|View full text |Cite
|
Sign up to set email alerts
|

Remote observing capability with Subaru Telescope

Abstract: We've implemented remote observing function to Subaru telescope Observation Software system (SOSs). Subaru telescope has three observing-sites, i.e., a telescope local-site and two remote observing-sites, Hilo base facility in Hawaii and Mitaka NAOJ headquarter in Japan. Our remote observing system is designed to allow operations not only from one of three observing-sites, but also from more than two sites concurrently or simultaneously. Considering allowance for delay in observing operations and a bandwidth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The broad spectral features indicated a large expansion velocity similar to the type Ic hypernovae SN 1998bw and SN 1997ef Hjorth et al 2003;Kawabata et al 2003;Matheson et al 2003;Mazzali et al 2003;Kosugi et al 2004). This was direct spectroscopic evidence that at least some classical GRBs originate from corecollapse supernovae.…”
Section: Multiwavelength Observations Of Grb 030329mentioning
confidence: 88%
“…The broad spectral features indicated a large expansion velocity similar to the type Ic hypernovae SN 1998bw and SN 1997ef Hjorth et al 2003;Kawabata et al 2003;Matheson et al 2003;Mazzali et al 2003;Kosugi et al 2004). This was direct spectroscopic evidence that at least some classical GRBs originate from corecollapse supernovae.…”
Section: Multiwavelength Observations Of Grb 030329mentioning
confidence: 88%
“…Keck has shown that solutions can be both adaptable and scalable by serving facilities with similar instrument control interface designs such as those at the UCO/ Lick Observatory including the 1 m Nickel (Grigsby et al 2008). Other professional class optical and near-infrared telescopes providing detailed literature on their remote capabilities include Subaru (Kosugi et al 2004), the Canada-France-Hawaii Telescope (CFHT; Vermeulen et al 2014), the NASA Infrared Telescope Facility (IRTF) (Bus et al 2002) and the Southern Astrophysical Research Telescope (SOAR; Cecil et al 2002).…”
Section: Infrastructure For Fully Remote Operationmentioning
confidence: 99%
“…GRB030329: Because of the low redshift (z = 0.168) origin and bright optical afterglow (∼ 13 mag at 0.1 days), numerous follow-up observations were conducted at various wavelengths (e.g. Stanek et al 2003;Smith et al 2003;Tiengo et al 2003;Klose et al 2004;Kosugi et al 2004;Urata et al 2004;Tiengo et al 2004;Kuno et al 2004;Šimon et al 2004;Frail et al 2005;Kohno et al 2005;Smith et al 2005;Gorosabel et al 2005;van der Horst et al 2008). The 250-GHz monitoring follow ups were performed by the MAMBO-2 bolometer array on the IRAM 30-m telescope (Sheth et al 2003) and the IRAM Plateau de Bure Interferometer (PdBI) (Resmi et al 2005).…”
Section: Status and Achievements Of Sub-millimeter Afterglow Follow-upsmentioning
confidence: 99%